Influence of polyether ether ketone coping crown on the adaptation of implant abutment - Li, Xuesheng; Liu, Shuai; Tang, Yishi; Zhao, Yunshan; Su, Yingbin (Journal of the Pakistan Medical Association, 2024)
Objectives: To evaluate the influence of polyether ether ketone coping crown on the adaptation of implant abutment. Method: The vitro study was conducted at the Department of Prosthodontics, Hainan Stomatological Hospital, China, from October 2021 to March 2022, and comprised patients undergoing implant surgery on first molar. Patients were divided into two group, with group A patients receiving polyether ether ketone coping crowns, and group B receiving zirconia crowns. Replica technique was used to replicate the gap between the crowns and the abutments. The thickness of the silicone film was measured under the stereomicroscope, and the gap between the groups was compared. Data was analysed using SPSS 22. Results: In group A, mean marginal gap was 82.43±25.00um, and mean overall gap was 85.45±33.75um. In group B, the corresponding values were 65.09 11.69um and 78.04±26.67um. There was a significant difference in the adaptation between the groups at the marginal and overall measurement points (p lessthan 0.05). Conclusion: Marginal and internal adaptations of polyether ether ketone coping crown for abutment could be considered clinically acceptable. Key Words: Crowns, Dental abutment, Dental implants, Dental marginal adaptation, Polyetheretherketone.